1963
DOI: 10.1055/s-0038-1654960
|View full text |Cite
|
Sign up to set email alerts
|

Procoagulant Material From Human Urine in Prothrombin Activation

Abstract: SummaryThe procoagulant or P fraction obtained from human urine was analyzed to determine how it functions in the activation of purified prothrombin. Prothrombin converts to thrombin in the presence of P fraction, Ac-globulin, calcium chloride and either whole platelets or platelet factor 3. The yield of thrombin can be made to depend upon the concentration of P fraction. This conversion of prothrombin to thrombin can be partially or completely inhibited by adding various concentrations of soybean trypsin inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1967
1967
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…54 It was later found that urinary PCA catalysed the conversion of prothrombin to thrombin only in the presence of platelet factor 3, factor V and Ca 2+ -a prothombinase type of activity, and was therefore classified as a 'platelet cofactor' rather than TF. 55,56 Aoki and von Kaulla further investigated the interaction between platelet factor 3, factor V, prothrombin, and urinary PCA. 57 They concluded that platelet factor 3 could be replaced by phospholipids in the activation of prothombin with partially purified urinary procoagulant (uPC), provided that the lipid was used under optimal conditions.…”
Section: Utf-a Historical Perspectivementioning
confidence: 99%
“…54 It was later found that urinary PCA catalysed the conversion of prothrombin to thrombin only in the presence of platelet factor 3, factor V and Ca 2+ -a prothombinase type of activity, and was therefore classified as a 'platelet cofactor' rather than TF. 55,56 Aoki and von Kaulla further investigated the interaction between platelet factor 3, factor V, prothrombin, and urinary PCA. 57 They concluded that platelet factor 3 could be replaced by phospholipids in the activation of prothombin with partially purified urinary procoagulant (uPC), provided that the lipid was used under optimal conditions.…”
Section: Utf-a Historical Perspectivementioning
confidence: 99%
“…The mean platelet count after the injection (268.4 ± 85.5 thousands/mm 3 ) was lower than the mean platelet count before the injection (279.6 ± 86.0 thousands/ mm 3 ) . This fall in the mean platelet count is significant (t = 2.575, 0 .02<p < 0.05) ( Table 7).…”
Section: Effect Of Urokinase Injection On Platelet Aggregationmentioning
confidence: 64%
“…This includes autoprothrombin II and platelet cofactor I (F-VIII) (26). Furthermore, a fraction from urine serves as a platelet cofactor (28) . The urine component is, however, distinguished from the others by its independently strong procoagulant activity (29).…”
Section: Discussionmentioning
confidence: 99%